Gedung Rektorat Universitas Darussalam Gontor Ponorogo (Penekanan pada konsep Eco Office) - Lutfi Haritsah, Ahmad; , Ronim Azizah, ST. MT; , Suryaning Setyawati ST, MT (2015)
Darussalam University of Gontor Ponorogo is a higher education of institutions with boarding scholl system using arabic and english for daily conversation. Founded ini 1963 untill now, Darussalam university continues to grow rapidly in terms of the quality of teaching, training, and educational services to be achieved in accordance with the vision and mission carried by UNIDA Gontor. Nowdays condition of facilities and infrastructure owned by UNIDA Gontor will be sufficient as a college, but with the rapid development that has been archieved, then UNIDA Gontor requires the development of a more complete and adjustments and sufficient to meet the guidance of educational services has been achieved and are constantly being developed and planned by UNIDA Gontor. Among the facilities and infrastructure that is not owned by UNIDA Gontor is the dead office of the universtity's academic and administrative buildings or widely known as a university rector building completed in terms of facilities, office spaces etc. And building the meeting to hold some events such as seminars, training and graduation ceremony and central library building. By trying to minimize impacts on the natural environment or human and produces a better life and more healthy, then applied eco office concept or eco-friendly office and simultaneously support the green building movement that has been widely applied to buildings ini Indonesia and even around the world to reduce the impact of global warming.